PENGEMBANGAN MODUL AJAR DESIGN THINKING UNTUK MENUNJANG DEEP LEARNING - Syahrina Harlin, Elieza; Fatah, Abdul; Yuhana, Yuyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low understanding of students' concepts on the quadratic function material and learning that is still centered on the teacher so that it does not support the achievement of deep learning. The purpose of this study is to describe: 1) the process of developing a Design Thinking-based teaching module to support Deep Learning on the quadratic function material at SMA Negeri 1 Baros, 2) the validity and practicality of the results of developing the Design Thinking teaching module to support Deep Learning, and 3) student responses to the use of the Design Thinking teaching module to support Deep Learning. This research is a research and development or Research and Development (R&D) using the Design Thinking model which consists of five stages, namely Empathize, Define, Ideate, Prototype, and Test. The results of the study show that: the Design Thinking teaching module to support Deep Learning is stated Validation of the teaching module was carried out by 2 material experts and 2 media experts. The material and media aspects with an average percentage of 83.83% are categorized as “Very Valid”. The practicality of the teaching module was measured using a teacher response questionnaire after the field trial completed by 3 mathematics teachers with an average percentage of 88.27% being categorized as “Very Practical”. Learning using the developed teaching module is able to support deep learning because it facilitates students to explore with GeoGebra, group discussions, and concept discovery activities through contextual problems.